US Rural Surgeons Leading During COVID-19: Where Are They Now?. Issue 8 (August 2021) - Sarap, Michael; Conyers, Julie; Cunningham, Crystal; Deutchman, Adam; Levine, Glenn; Long, Sue; Molt, Patrick; Rossi, Matt; Welsh, David; Hughes, Dorothy
Rural surgeons from disparate areas of the United States report on the effects of the COVID-19 pandemic in their communities as the virus has spread across the country. The pandemic has brought significant changes to the professional, economic, and social lives of the individual surgeons and their communities.